Deep neck space infections : The impact of smoking and alcohol consumption to antibiotic sensitivity - Sarkanen, Milla (My University, 2022)
Purpose The aim of this study is to review bacteriology and microbiological sensitivity of the deep neck space infections (DNIs) to detect the significance of bacterial resistance in the treatment of patients. The purpose is to detect antibiotic resistance to the most used antibiotics and find out whether the antibiotic resistance is related to the treatment days needed in ICU and patient features such as age, alcohol consumption, smoking and using drugs. Methods The retrospective analysis includes data of 277 patients with deep neck space infection from 2004 to 2015. Microbiological samples were collected from purulent secretion of the abscesses operated and drained. 66,4% of the samples in culture were positive (184 patients). The interest in this study is allocated towards Viridans-group streptococci and other streptococci. 103 patients’ microbiological culture contained the forementioned species and 92 of these patients were tested for antimicrobial susceptibility in Turku University Hospital. Results 103 patients were found with Viridans-group streptococci and other streptococci subspecies. 92 of them had antibiotic susceptibility tested and 10 patients were found with antibiotic resistance. 30 patients were found with Streptococcus Anginosus and 2 of them had resistance to clindamycin (6.7%). Patients with antibiotic resistance needed more treatment days in intensive care unit with a p-value 0.042. In crosstabulation alcohol consumption and smoking were found to have significant relation to bacterial resistance.
Keywords: Deep Neck Space Infections, Alcohol, Smoking, Antibiotic Resistance